PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 004 SEBERANG TELUK HILIR KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Kasmarni Kasmarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the results of learning science in fourth-grade elementary school students who are still low. The purpose of this study was to improve the learning outcomes of science by applying the cooperative pair type think pair share (TPS) model. The results showed, seen from the basic score, students who completed 11 people with a percentage of 47.82%, while students who did not complete 12 people with a percentage of 52.17%. cycle I, students who completed 17 people with a percentage of 73.91% while students who did not complete 6 people with a percentage of 26.08%. cycle II, students who completed 20 people with a percentage of 86.95% while the incomplete 3 people with a percentage of 13.04%. From the results of the study, it can be concluded that by applying the cooperative learning model the think pair share (TPS) type can improve science learning outcomes of grade IV students of SD Negeri 004 Seberang Teluk Hilir Kecamatan Kuantan Tengah, Kabupaten Kuantan Singingi.